Statistical analysis on Morishita-Seggs Pharmaceuticals, Inc. (MSPI) - Bacud, Marie Joanne B. (College of Engineering, 2001)
The Morishita-Seggs Pharmaceuticals Inc. located in Mandaluyong City, manufactures pharmaceutical products in the form of tablets, capsules, syrup and suspension. The group chose to focus on the production of tablets due to its biggest demand share from distributors and its higher rejection rate as compared to other product lines. Through interviews with the Quality inspectors and through reviewing the production sheets it was found out that the main problem was the considerable amount of rejected products because these products were not meeting specifications. Through the use of brainstorming, Ishikawa diagram and Pareto charts, the possible causes of rejection were identified, which were the batches of materials, machines used, and the level of temperature utilized. A 2 factorial design was used to determine the effects of the factors under study and their interaction. A single factor experiment was used to determine if the batch of materials has an effect on the production of tablets. Using the statistical analysis tools necessary, it was found out that the machine, temperature, and their interaction have no significant effects on the response variables, which are the weight, thickness, and diameter. The batches of materials have no effect as well to the response variables. The only significant effect that resulted was the effect of temperature on the hardness of the tablet. A higher temperature results to a higher rate of rejection for tablet production.After analyzing the problem and identifying that only temperature had an effect on rejection, necessary recommendations were generated. One of the recommendations is to constantly monitor baking temperature. Since the study was limited to the data provided, the group recommends to the company for them to bake their tablets at 60 degree celcius because it produced lesser rejects than those baked on 70 degree celcius. However, 60 degree celcius may not the optimal temperature that produces the least number of rejects. In order to determine the best temperature, further experiments should be conducted at various temperature.